Intelligent reconstruction of pipe system for BIM enabled maintenance - Xie, Hang (Nanyang Technological University, 2023)
Building Information Modeling (BIM) is nowadays a widely accepted technique that has changed the building industry radically. Compared to traditional 2D engineering drawings that are usually in the form of orthographs on papers, BIM provides convenient views from different angles. It presents engineers with abundant detailed information from accurate three-dimensional (3D) models. With the help of BIM, planning and design such as life span, energy cost, requirement for space and structure efficiency for construction will become much simpler. Thus, this author will develop a program that is based on the information provided by BIM to reconstruct part of the pipe system, which is fire protection system. During the development, three sample point cloud files that consist of different environmental conditions are applied in order to ensure the generalization of the program. The main purpose of testing on the point clouds is to skip the input for many parameters, thus making the program mostly automatic. The program eventually provides accurate recognition of fire protection systems’ components and acceptable related bounding boxes size, with an average run time of 20s. In other words, this program is overall capable of doing proper reconstruction for fire protection system. (Zhen-Zhong Hu et al., 2018)